2019
DOI: 10.3791/60102
|View full text |Cite
|
Sign up to set email alerts
|

Ion Mobility-Mass Spectrometry Techniques for Determining the Structure and Mechanisms of Metal Ion Recognition and Redox Activity of Metal Binding Oligopeptides

Abstract: Electrospray ionization (ESI) can transfer an aqueous-phase peptide or peptide complex to the gas-phase while conserving its mass, overall charge, metal-binding interactions, and conformational shape. Coupling ESI with ion mobility-mass spectrometry (IM-MS) provides an instrumental technique that allows for simultaneous measurement of a peptide's mass-to-charge (m/z) and collision cross section (CCS) that relate to its stoichiometry, protonation state, and conformational shape. The overall charge of a peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Our previous ESI-IM-MS amb analyses, have shown that the negatively-charged complexes are of particular interest because they correlate to the charge states that relate to the protonation state of the Cys, His, or carboxyl termini which are the potential metal ligand sites and they exhibit a distinct pH-dependence. [8][9][10][11][12][13][14][15] In Figure 3 we show the identity and the relative percentage of these negatively charged complexes for amb 5 G to R. Only G primarily formed the [amb 5 -6H+2Ni(II)] 2complex that related to six negatively-charged sites on the amb 5G peptide. Species G, as in the Co(II) analyses, also formed the negatively charged dimer binding 2Ni(II), [diamb 5ox -6H+2Ni(II)] 2-, where the 2Cys oxidized to form a disulfide bond.…”
Section: Comparative Ni(ii) Chelation By Amb 5a-r At Ph 70mentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous ESI-IM-MS amb analyses, have shown that the negatively-charged complexes are of particular interest because they correlate to the charge states that relate to the protonation state of the Cys, His, or carboxyl termini which are the potential metal ligand sites and they exhibit a distinct pH-dependence. [8][9][10][11][12][13][14][15] In Figure 3 we show the identity and the relative percentage of these negatively charged complexes for amb 5 G to R. Only G primarily formed the [amb 5 -6H+2Ni(II)] 2complex that related to six negatively-charged sites on the amb 5G peptide. Species G, as in the Co(II) analyses, also formed the negatively charged dimer binding 2Ni(II), [diamb 5ox -6H+2Ni(II)] 2-, where the 2Cys oxidized to form a disulfide bond.…”
Section: Comparative Ni(ii) Chelation By Amb 5a-r At Ph 70mentioning
confidence: 99%
“…Previous electrospray -ion mobility -mass spectrometry (ESI-IM-MS) studies of methanobactin 6,7 from Methylosinus trichosporium (mb-OB3b) and the amb peptides whose primary structure replaced the two enethiol oxazolone of mb-OB3b with the 2His-2Cys substituent groups of a zinc finger protein, have shown their potential for applications as affinity tags. [8][9][10][11][12][13][14][15] For example, the ESI-IM-MS analyses of the amb peptides shows that their formation of metal complexes are dependent on pH which is important for controlling the capture and release of tagged proteins in an IMAC column. A major attribute for ESI-IM-MS analyses is that it allows for the pH-dependent behavior of specific m/z conformers to be examined.…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive peptides with biological activities (e.g., antioxidant, antihypertensive, and anticancer activity) based on their amino acid composition and their primary sequence have been produced by enzymatic hydrolysis . Metal-ion chelation is a functional property commonly investigated in the literature. , Indeed, metals ions such as iron, zinc, calcium, and copper are essential for several biological functions such as enzyme catalysis, oxygen transport, and neurotransmitter release . However, their bioavailability is poor due to their low solubility in human fluids .…”
Section: Introductionmentioning
confidence: 99%
“…However, their bioavailability is poor due to their low solubility in human fluids . Metal-chelating peptides (MCPs) contribute to mineral absorption and bioavailability, thus regulating ion concentrations through selective bindings . Finally, iron- and copper-chelating peptideswhile complexing these transient metal ionscan act as indirect antioxidants by inhibiting in vivo the Fenton and Haber–Weiss reactions responsible for the formation of reactive oxygen species (including the hydroxyl radical) and subsequent radical chain reactions.…”
Section: Introductionmentioning
confidence: 99%
“…3 Ion mobility -mass spectrometry (IM-MS) [3][4][5] with molecular modelling and novel ion activation methods can be used to determine the accurate structure of these zinc containing metallopeptides. Previous studies of methanobactin 6,7 from Methylosinus trichosporium and analogue methanobactin (amb) peptides [3][4][5][8][9][10][11] show the IM-MS analyses in negative ion mode is particularly informative because it shows a distinct pH dependence for the metal binding and provides the protonation state of the acidic and basic binding sites, the charge of the metal ion, and the collision cross section of the conformer. The primary structures of the amb peptides include Pro as a hinge to position the His and Cys substituent groups for coordinating the metal ion ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%